Metacognitive Learning Strategies Used by the Sixth Semester Student of English Education Department of Universitas Cendrawasih Papua in Learning Speaking Skill - Nicodemus Bise (Jurnal Keguruan dan Ilmu Pendidikan, 2017)
Metacognitive Learning Strategies used by The Sixth Semester Student of English Education Department of Universitas Cendrawasih Jayapura in Learning Speaking Skill. The objective of this research was to find out the metacognitive learning strategies commonly used by the fifth semester students in developing their speaking ability and whether the good students and weak students used the same metacognitive learning strategies in developing their speaking ability. The method used was descriptive, using percentage technique. The samples consisted of 35 fifth semester students of English Education Department of UNCEN Jayapura in 2014/2015 academic year. The data collected through questionnaires. The research concluded that good students approximately always used the all metacognitive learning strategies. The most commonly strategy used by good students is selective attention and the most rarely used is delayed production. The percentages of other strategies were nearly the same. The most commonly strategy used by weak students is delayed production the most rarely used is advance organizer. The percentages of other strategies were nearly the same.